The Italian Way to Carsharing - Laurino, Antonio; Grimaldi, Raffaele (TeMA - Journal of Land Use, Mobility and Environment, 2012)
Carsharing (CS) is increasing its role worldwide as an alternative transport mode, often more sustainable than private transport with self-owned vehicles. We first focus on the main characteristics of those services and on the impacts they generated, starting from the analysis of the literature on this topic. CS initiatives are growing everywhere, however numbers are still minor and impacts are still far from a level that can deliver significant aggregate benefits. This paper studies the existing Italian carsharing experiences, trying to understand its strengths, that have allowed its development, but also possible limits and weaknesses. The presence of a national coordination structure (Iniziativa Carsharing - ICS), unique in Europe and created to boost local initiatives providing standardisation and interoperability, surely helped the development of the system. Some initiatives have been successful in terms of membership (in particular Milan, Venice and Turin), but others have been discontinued. Italian users’ characteristics are similar to the ones of users abroad: the majority of users are well educated male, living in small households having one or no cars and using public transport every day. At present, Italian drivers generally still show a scarce propensity to share their cars, considered more as “goods” than as “services”. A case study in Milan, the first and most successful initiative in Italy, shows a significant increase in CS membership after the implementation of a city charging scheme (“Ecopass” at first, then “Area C”). Moving shared cars from garages to “on the street parking” has proved successful too. The usage of the service has changed in time: users have increased (+151%) more than runs (+137%) – 2006 to 2009, while average length and duration of each run have decreased (-30% and -43% respectively, 2006 to 2010). Milan’s initiative also put s into practice many incentives for users that likely contributed to its success, i.e. free access to limited traffic zones, use of public transport reserved lanes, free parking in tolled spaces and discounts on the annual fee for public transport season ticket holders. The result of CS initiatives in the future will likely depend largely on mobility policies that both the national government and municipalities will introduce in the future. A legislation concerning CS is needed in order to promote the involvement of private initiatives, while mobility policies should evidence the advantages, both in economical and practical terms, offered by CS with respect to a private car, also considering the social role that CS might have for low-income households (and students), that could have access to a car on a “pay as you use” principle. CS benefits from broader transport policies and can improve their social acceptability, by integrating existing public transport systems – in terms of flexibility, land coverage and availability in time.